Groundwater occurrence in cold environements : examples from Nunavik, Canada - Cochand, Marion; Ouellet, Michel; Therrien, René; Talbot Poulin, Marie-Catherine; Murray, Renaud; Banville, David-Roy; Lemieux, Jean-Michel; Fortier, Richard; Molson, John W. H. (Hydrogeology Journal, 2018)
Water availability and management issues related to the supply of drinking water in northern communities are problematic in Canada. While rivers and lakes are abundant, they are vulnerable to contamination and may become dry in winter due to freezing. Groundwater can often provide a more secure and sustainable water source, however its availability is limited in northern Canada due to the presence of permafrost. Moreover, the exploitation of northern aquifers poses a dual challenge of identifying not only permafrost-free areas, but also permeable areas which will allow groundwater recharge and exploitation. Suitable aquifers are not as common in northern Canada since the shallow subsurface is mostly composed of low-permeability crystalline rocks or unconsolidated sediments of glacial origin that are highly heterogeneous. In order to investigate groundwater occurrence and associated geological contexts in Nunavik (northern Quebec, Canada), along with exploring how these resources will evolve in response to climate change, field and compilation work were conducted in the surroundings of the four villages of Salluit, Kuujjuaq, Umiujaq and Whapmagoostui-Kuujjuarapik. These villages are located in different permafrost zones, ranging from continuous to discontinuous, as well as in different geological environments. It was found that despite the ubiquitous presence of permafrost, unfrozen aquifers could be identified, which suggests that groundwater may be available as a source of drinking water for small communities. Expected climate change, with predicted permafrost thawing and increases in temperature and precipitation, should enhance groundwater availability and may contribute to a more secure source of drinking water for northern communities.